A study on the performance of limestone filter for the treatment of domestic wastewater - Suhara, Sidek (2010)
Alternative wastewater treatment systems combat many on-site disposal problems, but no incentives are given to householders to improve the domestic wastewater quality disposal. Untreated wastewater has harmful effects on the environment. Household wastewater or sewage may has disease-causing bacteria, infectious viruses, and household chemicals. If too much untreated sewage is released to the environment, dissolved oxygen level may drop and some species of fishes and other aquatic life may die. There are many methods and techniques involved in treating domestic wastewater. The present study is to investigate the ability of limestone to treat the domestic wastewater in reducing the quality of pollution before it can be discharge to environment. Sample of wastewater was taken from sewerage treatment plant at Taman Melayu Gambang. The wastewater quality analysis has been carried out to obtain the characteristic of wastewater such as turbidity, suspended solids, BOD, COD, pH and heavy metal. This operating system involved the used of limestone drains with the constant flow. The size of limestone were vary ranging from the small size ( 3.35mm and 6.35rmn), medium size (10.0mm) and large size (15 mm and 20mm). The experimental results indicate that limestone filter has removed turbidity ranging from of 8.31% to 19.658%,pH increase ranging from 6.26% to 19.658%,total suspended solid removed from 24% to 84.82%, BOD removed from 11.37% to 53.38%, manganese removed from 96.47% to 99.7%,zinc removed from 83.87% to 99.63%, lead removed from 83.58% to 100%, copper removed from of 83.58% to 100 % and Ferum remove from 42.09 % to 94.39%.The removal efficiency of limestone filter depends on the size of filter media and contact times with the wastewater. The bigger size of filter media gave thelower removal efficiency than smaller filter media. At higher contact times (60 mm), the removal efficiency was higher than at lower contact times (30 mm) . Overall, filtration using limestone is an appropriate technic for the treatment of wastewater because it could reduce organic solids and heavy metal which offer low cost investment.